The Essence and Importance of Hospice Homes, Performance Appraisal - kizi, Ziyaeva Holida Omonqul; Mingbayeva, B. J. (European Journal of Life Safety and Stability (2660-9630), 2022)
In this article, the concept of hospice, the rules of the hospice Congress, as well as the registration of a person in the hospice, means that he can not only receive powerful pain relievers that relieve his pain, but also receive highly qualified psychological help, can correctly receive his diagnosis and again try to overcome the disease, and can apply not only to people on the.